Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Media Flashcard Berbasis Gamifikasi terhadap Kemampuan Pemecahan Masalah dan Hasil Belajar Siswa pada Mata Pelajaran IPA Kelas VII - Ehva Pahria Ummul Khaer; Jailani; Sri Purwati; Suparno Putera Makkadafi; Vandalita Maria Magdalena Rambitan (UNIB Press, 2026)
Low student science learning outcomes are characterized by low learning engagement, poor problem-solving skills, some students not yet mastering basic material, and the failure to implement media-assisted Problem-Based Learning (PBL) learning models. This study aims to determine the effect of the Problem-Based Learning model, assisted by gamification-based flashcards, on students' learning outcomes and problem-solving abilities in seventh-grade science. The study used a quantitative approach with a quasi-experimental design and a pretest-posttest nonequivalent control group design. The sample was selected using purposive sampling, with 50 students from grades VII-8 as the control class and VII-9 as the experimental class. Data analysis was performed using the N-Gain test and independent samples t-test. The results showed that the average N-Gain for the control and experimental classes were in the moderate category, at 0.58 and 0.63, respectively. The independent samples t-test obtained a significance value of 0.000 < 0.05 for problem-solving ability and 0.032 < 0.05 for learning outcomes, thus rejecting H₀ and accepting Hₐ. Based on these results, it can be concluded that the implementation of the Problem-Based Learning model assisted by gamified flashcard media has an impact on students' problem-solving abilities and learning outcomes in the science subject of ecology and biodiversity in seventh grade.